Synaptotagmins at the endoplasmic reticulum–plasma membrane contact sites maintain diacylglycerol homeostasis during abiotic stress. Issue 7 (4th May 2021) - Ruiz-Lopez, Noemi; Pérez-Sancho, Jessica; del Valle, Alicia Esteban; Haslam, Richard P.; Vanneste, Steffen; Catalá, Rafael; Perea-Resa, Carlos; Damme, Daniël Van; García-Hernández, Selene; Albert, Armando; Vallarino, José; Lin, Jinxing; et al.
Abstract: Endoplasmic reticulum–plasma membrane contact sites (ER–PM CS) play fundamental roles in all eukaryotic cells. Arabidopsis thaliana mutants lacking the ER–PM protein tether synaptotagmin1 (SYT1) exhibit decreased PM integrity under multiple abiotic stresses, such as freezing, high salt, osmotic stress, and mechanical damage. Here, we show that, together with SYT1, the stress-induced SYT3 is an ER–PM tether that also functions in maintaining PM integrity. The ER–PM CS localization of SYT1 and SYT3 is dependent on PM phosphatidylinositol-4-phosphate and is regulated by abiotic stress. Lipidomic analysis revealed that cold stress increased the accumulation of diacylglycerol at the PM in a syt1/3 double mutant relative to wild-type while the levels of most glycerolipid species remain unchanged. In addition, the SYT1-green fluorescent protein fusion preferentially binds diacylglycerol in vivo with little affinity for polar glycerolipids. Our work uncovers a SYT-dependent mechanism of stress adaptation counteracting the detrimental accumulation of diacylglycerol at the PM produced during episodes of abiotic stress. Abstract : Arabidopsis synaptotagmins 1 and 3 are localized at endoplasmic reticulum–plasma membrane contact sites and during abiotic stress episodes control diacylglycerol homeostasis at the plasma membrane